Development of Aquaculture Leading Sector to Improve Economic Development of Banjar Regency - Herlina Maulidah; Deasy Arisanti (The Innovation of Social Studies Journal, 2025)
The contribution of the basic sector to the economy of a region makes this basic sector often referred to as the leading sector. The role of leading sectors has a big impact on increasing the economic development of an area. Theoretically, the leading sectors play a role in encouraging economic growth by increasing employment opportunities. This research aims to analyze the leading sectors of and understand the potential of the financial sector in Banjar Regency. The analytical methods used in this research are Location Quotient (LQ) and Klassen Typology. The secondary data used in this research is the annual data available on the Badan Pusat Statistik (BPS) Banjar Regency and the Badan Pusat Statistik (BPS) South Kalimantan Province websites for the 2014-2023 period. The results of the Location Quotient analysis show that there are 11 base sectors. Additionally, the result of the Klassen Typology analysis emphasizes the availability of five sectors in quadrant I. One of the base sectors and also a potential sector that can still develop rapidly in Banjar Regency is the Agriculture, Forestry, and Fisheries sector. The fisheries sub-sector has the potential to be developed in aquaculture. This research will provide an overview of what policies are appropriate to improve existing sectors in Banjar Regency.